THE USE OF FLASHCARDS ON STUDENT VOCABULARY MASTERY - Dina Khairani; Nur Azizah Nasution (Journal of Advances in Linguistics and English Teaching (JALET), 2025)
To improve students' vocabulary mastery, this qualitative study looks at how effective flash cards are. This study investigates how using flash cards affects students' retention and recall of newly learned vocabulary through observational approaches. The results demonstrate how successful flash cards are when used in vocabulary education, showing a considerable improvement in both retention and recall speed among students who use them. According to these findings, using flash cards in conjunction withvocabulary learning techniques can have a Prominent positive impact on  language learning. Flash cards provide a useful and effective method for learning a language by encouraging improved retention and speedier recall of vocabulary. For teachers looking to improve language learning outcomes in the classroom, this implies encouraging consequences. Flash cards can be an effective technique for helping children increase their vocabulary, which will ultimately help them succeed academically and in language classes. The study's overall conclusions highlight the value of cutting-edge teaching techniques, such the use of flash cards, in encouraging efficient language learning practices and improving student performance in language learning initiatives.